2017
DOI: 10.3354/aei00205
|View full text |Cite
|
Sign up to set email alerts
|

Potential of aquacultural sludge treatment for aquaponics: evaluation of nutrient mobilization under aerobic and anaerobic conditions

Abstract: In recirculating aquaculture systems (RAS), mechanical removal of suspended solids by clarifiers or drum filters provides an organic mixture rich in nutrients. Still, in most traditional RAS, this sludge is discharged directly or following dewatering. Here, the potential recycling of nutrients from sludge is assessed, comparing aerobic and anaerobic mobilization of nutrients experimentally, ultimately aiming at an application in aquaponic systems. Nutrient mobilization processes were studied, monitoring solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 28 publications
6
56
0
Order By: Relevance
“…There is a relatively large internet-or web-based store of aquaponic information, but much of this is anecdotal, with little scientific or technical engineering basis. Claims of increased water use efficiency compared to soil-based farming [15] are regularly made, as are claims of better sustainability and decreased environmental impact [3,[16][17][18][19]. However, little by way of comparative, scientific data are available to justify such claims.…”
Section: Introductionmentioning
confidence: 99%
“…There is a relatively large internet-or web-based store of aquaponic information, but much of this is anecdotal, with little scientific or technical engineering basis. Claims of increased water use efficiency compared to soil-based farming [15] are regularly made, as are claims of better sustainability and decreased environmental impact [3,[16][17][18][19]. However, little by way of comparative, scientific data are available to justify such claims.…”
Section: Introductionmentioning
confidence: 99%
“…One potential solution for dealing with sludge is through improved digestion of their organic matter in order to solubilize nutrients for use in aquaponic systems. In this context, anaerobic and aerobic sludge digesters can utilize micro-organisms to break down the sludge into bioavailable nutrients that can subsequently be used for plant nutrition (Delaide et al, 2018;Monsees et al, 2017). In decoupled aquaponic systems (DAPS), as proposed by Goddek et al (2016), Goddek and Keesman (2018), bioreactors for sludge treatment can be designed to both reduce waste production and optimise nutrient re-utilisation (Goddek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To-date, very few studies have reported on the potential of aerobic and anaerobic digestion of fish sludge as a means to recover nutrients in aquaponics systems (Delaide et al, 2018;Monsees et al, 2017). In most studies on aquaculture sludge digestion in UASBs, the main focus has been on reducing COD and producing methane (CH4) from solids (Mirzoyan et al, 2010;Mirzoyan and Gross, 2013;Van Rijn, 2013;Zhang et al, 2013) rather than the potential for recovery of macro and microelements and reduction in wastes.…”
Section: Introductionmentioning
confidence: 99%
“…; Monsees et al . ), the removal of heavy metals from water (Zheng et al . ) and reduced solid waste material (Pantanella et al .…”
Section: Economic Considerations: Do We Know ‘Whether’ Commercial Aqumentioning
confidence: 99%